Histopathological pattern of gynaecological malignancies: National Health Laboratory (NHL), Sudan - Rayis, Duria Abdelwahab; Zulfu, Azza; yassin, khalid ahmed; Merghani, Alwiya; Fageary, Asma Mohamed; Raheem, Dr Sawsan Abdel (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Background: Gynaecological malignancies (GM) is a common cancer problem in both developing and developed countries .The burden of GM is more critical in developing countries, this is due to lack or deficient screening and late clinical presentation. The aim of this study is to study the histopathological pattern of GM in the NHL (National Health Laboratory) Sudan. Material &Methods: Clinical data, histopathological reports, stained tissue slides of patients diagnosed histologically as GM were revised from the archive of the department of histopathology and cytology at the NHL . Results: 372 patients diagnosed histologically as GM from 1st Jan 2009-31st Dec to the 1st Jan 2013 were studied. The commonest GM histological type was cervical malignancies, followed by ovarian, endometrial, vaginal, vulvar, choriocarcinoma and tubal cancer respectively .Conclusion: There is an urgent need for screening, early detection and prompt management for GM. Keywords: GM, NHL, histopathological pattern